Applicability of BaTiO3/graphene oxide (GO) composite for enhanced photodegradation of methylene blue (MB) in synthetic wastewater under UV–vis irradiation. (December 2019) - Mengting, Zhu; Kurniawan, Tonni Agustiono; Fei, Song; Ouyang, Tong; Othman, Mohd Hafiz Dzarfan; Rezakazemi, Mashallah; Shirazian, Saeed
Abstract: Methylene blue (MB) is a dye pollutant commonly present in textile wastewater. We investigate and critically evaluate the applicability of BaTiO3 /GO composite for photodegradation of MB in synthetic wastewater under UV–vis irradiation. To enhance its performance, the BaTiO3 /GO composite is varied based on the BaTiO3 weight. To compare and evaluate any changes in their morphologies and crystalline structures before and after treatment, BET (Brunauer–Emmett–Teller), XRD (X-ray diffraction), FTIR (Fourier transform infrared spectroscopy), SEM (scanning electron microscopy) and TEM (transmission electron microscopy) tests are conducted, while the effects of reaction time, pH, dose of photocatalyst and initial MB concentration on its photodegradation by the composite are also investigated under identical conditions. The degradation pathways and removal mechanisms of MB by the BaTiO3 /GO are elaborated. It is evident from this study that the BaTiO3 /GO composite is promising for MB photodegradation through ·OH. Under optimized conditions (0.5 g/L of dose, pH 9.0, and 5 mg/L of MB concentration), the composite with 1:2 dose ratio of BaTiO3 /GO has the highest MB degradation rate (95%) after 3 h of UV vis irradiation. However, its treated effluents still could not comply with the discharge standard limit of less than 0.2 mg/L imposed by national environmental legislation. This suggests that additional biological treatments are still required to deal with the remaining oxidation by-products of MB, still present in the wastewater samples such as 3, 7-bis (dimethyl-amino)-10H-phenothiazine 5-oxide. Graphical abstract: Image 1 Highlights: BaTiO3 /GO-66% composite was effective for 95% of MB removal. The same composite has 1:2 dose ratio of BaTiO3 /GO. Optimum conditions: 0.5 g/L of dose; pH 9.0; 5 mg/L of MB concentration; 3 h of reaction time.